Investigating English to Indonesian Live Simile Translation - ismarita ramayanti; Nabila Maudy Prameswari (STBA LIA - Jakarta, 2020)
This study focuses on English to Indonesian live simile translation. Live simile is the mostly occurred in novels, but unfortunately, under-researched. 33 live similes were collected from a novel and 12 data were chosen randomly to be analyzed using descriptive qualitative method. The comparison markers used to identify the live simile were based on Pierini’s and the procedures applied to analyze the data were based on Newmark’s. The study concluded that the comparison marker mostly used was verb-like and the mostly used translation procedure was reproducing the same image in the translation. It was also revealed that culture has significant role in translating simile and therefore, translators need to relate their culture knowledge in the source language in order to reproduce the same image in the translated text.